Employers and Employers Associations in the Netherlands Industrial Relations Systems - Windmuller, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1967)
This article analyzes the organization of employers in the Netheriands for their industrial relations tasks. After first describing the role of individual employers and explaining why that role is a relatively small one, the article emphasizes the structure and functioning of employers associations in industrial relations. Special attention is given to the existence of pluralistic associations in a country where by tradition most if not all social organizations are pluralistically organized. The postwar wage and economic policies of the Dutch government have encouraged a high degree of centralized decision-making among employers as well as among labor organizations. The article concludes with some observations about the likely consequences of a current trend toward greater decentralization.